Molecular Circuits of Resolution in the Eye - Elvira L. Liclican; Karsten Gronert (The Scientific World Journal)
Lipid autacoids have well-established key roles in physiology and pathophysiology. Eicosanoids derived from ω-6 arachidonic acid (AA) have long been recognized for their roles in cardiovascular and renal functions, and vascular tone, as well as regulating inflammatory and immune functions. It is now appreciated that AA is a substrate for generating lipid mediators with anti-inflammatory and proresolving properties, namely lipoxins (i.e., LXA4), which are an integral component for the successful execution of beneficial and essential acute inflammatory responses. In addition to AA, the ω-3 polyunsaturated fatty acids (PUFAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) also serve as substrates to generate potent and protective autacoids, such as resolvins and neuroprotectin (i.e., NPD1), respectively. These ω-3–derived signals may mediate the remarkable protective action of essential dietary ω-3 PUFAs. Formation and bioactivity of lipid mediators in the eye are relatively unexplored and of considerable interest, as the eye contains highly specialized tissues, including the transparent avascular and immune-privileged cornea, and the neuro-retina. A rapidly emerging field has identified key biosynthetic enzymes, receptors, and temporally defined endogenous formation of ω-3– and ω-6–derived protective lipid circuits in the eye. Protective endogenous roles of LXA4 and NPD1 have been established utilizing lipidomic analysis, knockout mice, and pharmacological, genetic, and dietary manipulation, providing compelling evidence that these intrinsic lipid autacoid circuits play essential roles in restraining inflammation, promoting wound healing, inhibiting pathological angiogenesis, and providing neuroprotection in the delicate visual axis.